The Isaac Cowie collection of Plains Cree material culture from Central Alberta / Fieldiana, Anthropology, new series, no.17 - VanStone, James W.; Field Museum of Natural History. (Chicago, Ill. : Field Museum of Natural History, 1991)
The collections of the Field Museum of Natural History contain 110 ethnographic objects collected among the Plains Cree of central Alberta in 1892 for the World's Columbian Exposition by Isaac Cowie, a retired Hudson's Bay Company trader living in Edmonton. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from previous studies of the Plains Cree, notably those of Mandelbaum (1940, 1979). Includes bibliographical references (p. 17-18). The collections of the Field Museum of Natural History contain 110 ethnographic objects collected among the Plains Cree of central Alberta in 1892 for the World's Columbian Exposition by Isaac Cowie, a retired Hudson's Bay Company trader living in Edmonton. The artifacts in this collection are described and illustrated. For comparative purposes, information is included from previous studies of the Plains Cree, notably those of Mandelbaum (1940, 1979). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).